Revisiting the internationalization of the yuan - Yongding Yu (Asian Development Bank Institute (ADBI), 2012)
As the world's second largest economy, largest trading nation, and the largest foreign holder of United States (US) government bonds, the People's Republic of China (PRC) needs a currency with international status that can match its economic status in the global economy. However, sequencing is important. Before the internationalization of the yuan can make meaningful progress, necessary conditions, such as the existence of deep and liquid financial markets, a flexible exchange rate and interest rates responsive to market conditions must be created. The process of yuan internationalization essentially is a process of capital account liberalization. Due to the unprecedented and complex global financial crisis and the PRC's huge imbalances, capital account liberalization has to be pursued in a cautious way. As a result, the internationalization of the yuan is bound to be a long-drawn process. The PRC's road map for the internationalization of the yuan is flawed with many missing links and wishful thinking. Yuan internationalization guided by the current road map may be proven counterproductive.
Keywords: F31; F33; 330; yuan internationalization; revisiting internationalization yuan; prc exports; Renminbi; Reservewährung; Kapitalbilanz; Finanzmarktregulierung; China